A térbeli alkotás oktatási jelentősége az általános iskolában - Lehot'áková, Eva; Tóth , Attila (Kultúratudományi Szemle, 2022)
The educational significance of spatial creation in primary school Eva Lehot’áková – Attila Tóth The time for learning to think spatially is limited in time. There are certain time periods for the development of spatial capacity vision. When these periods are missed, one loses the opportunity to develop their abilities to the level provided by his genetic disposition. Art education at primary schools has an educational potential to develop the spatial imagination of 10-12 year old students.